Building Capacity through Collaborative Local Action: Case of Matra REGIMA within Zeytinburnu Regeneration Scheme - Ozcevik, Ozlem; Beygo, Cem; Akcakaya, Imge (American Society of Civil Engineers (ASCE), 2010)
Following the 1999 Marmara earthquakes, urban regeneration has gained particular importance in redevelopment of housing areas particularly in historical districts of Istanbul. Local governments, upon new roles and responsibilities regarding postdisaster conditions as well as the changing global trends, called for innovative planning approaches which involve the community. In this respect, some questions are raised in the planning agenda: While performing the new roles, what kind of institutional changes should local governments experience? How should local community be involved in this process? The paper considers the conditions of spatial and community change in realizing urban regeneration as a collaborative action through the case study of Matra—Regeneration of Istanbul Metropolitan Area (Matra REGIMA) project which highlights the fundamental capacity building requirement for both local government practitioners and the community in order to achieve the necessary actions. Consequently, this study highli...